2015
DOI: 10.1007/s10682-015-9785-4
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic genetic differentiation along environmental and geographic gradients indicate divergent selection in a white pine species complex

Abstract: We explored the role of isolation by environment in a white pine species complex: Pinus flexilis, Pinus strobiformis and Pinus ayacahuite distributed from Canada to Central America. We predict that species differentiation would match genetic structure of candidate genes associated with significant differences in climatic niche in the species complex. To test this prediction, we sequenced five candidate genes for drought tolerance and three housekeeping genes, in individuals from across the entire range of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Thus, given sufficient time, even under a model of speciation with gene flow, such coupling effects will ensure the maintenance of species boundaries relative to the action of either factor alone (Barton & De Cara 2009). Specifically, in our focal species, previous work using candidate genes for drought stress provides evidence for divergent selection driving speciation, despite low genome-wide levels of differentiation (Moreno-Letelier & Barraclough 2015). Although a thorough examination of exome-wide variation remains to be done, the correlation of h with drought related variables when coupled with the work of Moreno-Letelier & Barraclough (2015) implies that adaptive responses to drought stress likely contributed to the origin and maintenance of species boundaries in this system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, given sufficient time, even under a model of speciation with gene flow, such coupling effects will ensure the maintenance of species boundaries relative to the action of either factor alone (Barton & De Cara 2009). Specifically, in our focal species, previous work using candidate genes for drought stress provides evidence for divergent selection driving speciation, despite low genome-wide levels of differentiation (Moreno-Letelier & Barraclough 2015). Although a thorough examination of exome-wide variation remains to be done, the correlation of h with drought related variables when coupled with the work of Moreno-Letelier & Barraclough (2015) implies that adaptive responses to drought stress likely contributed to the origin and maintenance of species boundaries in this system.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of islands of divergence is expected in conifers, given the prevalence of polygenic architectures defining continuous trait variation across species boundaries and the expected prevalence of soft sweeps (Pritchard & Rienzo 2010; Alberto et al 2013; Rajora et al 2016; Lind et al 2017). Alternatively, given the large and complex genomes of conifers (reviewed by De La Torre et al 2014a) our ddRADseq markers underrepresented genic regions, which are often identified as islands of divergence (Nosil & Feder 2012; Zhou et al 2014; Moreno-Letelier & Barraclough 2015; Marques et al 2017). For example, Moreno-Letelier & Barraclough (2015) demonstrated the potential for islands of divergence at drought-associated genes, which had a high average F ST value of 0.33 (0.09–0.4) compared to the genome-wide estimate from this study ( F ST-species = 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Islands of divergence are often expected only under certain genetic architectures and selection scenarios which have been shown to be less prevalent in conifers (Alberto et al., ; Lind et al., ; Pritchard & Di Rienzo, ; Rajora, Eckert, & Zinck, ). Alternatively, given the large and complex genomes of conifers (reviewed by De La Torre, Birol et al., ), our ddRADseq markers likely underrepresented genic regions, which are often identified as islands of divergence (Marques et al., ; Moreno‐Letelier & Barraclough, ; Nosil & Feder, ; Zhou, Zhang, Liu, Wu, & Savolainen, ). For example, Moreno‐Letelier and Barraclough () demonstrated the potential for islands of divergence at drought‐associated genes, which had a high average F ST of 0.33 (0.09–0.40) as compared to the genome‐wide estimate from this study ( F ST‐species = 0.02).…”
Section: Discussionmentioning
confidence: 99%